200 intellectuals converge on ‘Human Capital Development’ - UMP, PNC
For the first time, University Malaysia Pahang (UMP) conducted a gathering of 200 intellectuals in 35 parallel sessions in an International Conference on Human Capital Development (ICONHCD 2009) held at the Swiss Garden Resort & Spa in Kuantan from May 25 to 27 last year.